Performance standards for the GII. - Seitz, N.B (IEEE Communications magazine)
This article summarizes the traditional process for developing international telecommunication performance standards and describes enhancements that will be needed to adapt the process for use in the emerging global information infrastructure (GII). The necessary enhancements are being developed under the auspices of ITU-T Study Group 13